Comparative analysis on different software piracy prevention techniques - Ahmad Mohammad Hassan; Ayuba John (International Journal of Informatics and Communication Technology (IJ-ICT), 2021)
Numerous type of software piracy known today, have several prevention techniques which has been established against them. Although, different software piracy techniques have been established, but the choice of which one should be the best to develop any software is the challenge for most software developers. Consequently, example of the types of piracy in software development can be categorise as follows: cracks and serials, softlifting and hard disk loading, internet piracy and software forging, mischaneling, reverse engineering, and tampering. We have several types of prevention techniques which aimed to resolved piracy in software development, although the methods have been wrecked. In this work a critical analysis has been carryout on different software piracy techniques and a simple model software was designed using the best technique to validate the results of the analysis.